Increased matrix concentrations of IGFBP-5 in cancellous bone in osteoarthritis. Issue 9 (12th August 2004) - Sharp, C A; Brown, S J; Davie, M W J; Magnusson, P; Mohan, S
Abstract : Background: In osteoarthritis cancellous bone adapts to meet altered mechanical loading. These changes may be mediated by insulin-like growth factors (IGF-I and IGF-II), but the matrix bound binding protein, IGFBP-5 has not been investigated. Objectives: To measure IGF-I, IGF-II, and IGFBP-5 in femoral head bone from non-OA controls and patients with OA, and to relate these to apparent density (ρA ) and elastic modulus (Ec). Methods: ρA, Ec, and IGF system components were measured in cancellous bone from superior and inferior regions of femoral heads from 31 patients with OA and 11 age selected controls. Results: Ec and ρA were greater (p<0.05) in the superior region of all femoral heads. In primary OA, ρA was increased in the inferior region (p<0.05). IGFBP-5 was increased, about twofold, at superior and inferior regions in primary OA (1.60 and 1.54 ng/mg bone, respectively, both p<0.05) and in Paget's disease (2.44 and 1.75 ng/mg bone, both p<0.05) compared with controls (0.73 and 0.95 ng/mg bone). In controls, inverse correlations between IGFBP-5 and both ρA and Ec at superior ( r s  = −0.64 and −0.73, both p<0.05) and inferior regions ( r s  = −0.72, p<0.05 and −0.24 (NS)) were seen, but these were lost in OA. Conclusions: IGFBP-5 may modulate cancellous bone formation by negative feedback. In end stage OA this is disrupted, but has little influence on material properties.